2006
DOI: 10.3989/scimar.2006.70s279
|View full text |Cite
|
Sign up to set email alerts
|

Field comparison of sardine post-flexion larval growth and biochemical composition from three sites in the W Mediterranean (Ebro river coast, bays of Almería and Málaga)

Abstract: SUMMARY: Late larval stages of sardine (16-23 mm) were sampled during the 2003 spawning season in their nursery grounds located off the Ebro river mouth, on the Catalan coast, and in two bays of the Alborán Sea coasts, the Bay of Almería and the Bay of Málaga. The daily growth analysis of each sampled population revealed faster growth in the Ebro sardine larvae than in both of the Alboran Sea larval populations. This fact is supported by their greater content with age of DNA, RNA and protein. However, the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…In the Spanish Mediterranean waters, the indicated PSH areas are dominated by the narrow shelf of the North Alboran Sea, the Ebro River area, the Catalan Sea and the Balearic plateau, which matches the known sardine spawning grounds in the region (Pérez de Rubín 1996, Olivar et al 2003, García et al 2006, Vargas-Yáñez & Sabatés 2007. These areas generally match those indicated by the adult model in December, verifying that the patchiness of the eggs closely reflects the patchiness of the spawning adults.…”
Section: Potential Spawning Habitat (Psh)supporting
confidence: 61%
See 1 more Smart Citation
“…In the Spanish Mediterranean waters, the indicated PSH areas are dominated by the narrow shelf of the North Alboran Sea, the Ebro River area, the Catalan Sea and the Balearic plateau, which matches the known sardine spawning grounds in the region (Pérez de Rubín 1996, Olivar et al 2003, García et al 2006, Vargas-Yáñez & Sabatés 2007. These areas generally match those indicated by the adult model in December, verifying that the patchiness of the eggs closely reflects the patchiness of the spawning adults.…”
Section: Potential Spawning Habitat (Psh)supporting
confidence: 61%
“…1 & 7), a pattern that matches the former sardine spawning grounds in the Spanish Mediterranean waters (Pérez de Rubín 1996, Olivar et al 2003, Vargas-Yáñez & Sabatés, 2007. Suitable spawning areas visually correspond to sardine adult potential distributions, which agrees with the coincidence between early winter and the beginning of the spawning season for sardine in the Mediterranean (García et al 2006 and references therein, Soma ra kis et al 2006). PSH areas were also indicated in other parts of the Mediterranean as well as in the coastal waters of Africa (Fig.…”
Section: Habitat Mappingsupporting
confidence: 54%
“…Supporting this theory, García et al (2006) found that RNA/DNA ratios did not increase with SL in late larval stages of Sardina pilchardus. According to this, an upper limit in larval condition or RNA/DNA ratio is reached at a certain size -at the asymptotic valueafter which, despite further increase in size, larval condition or RNA/DNA ratio remain fairly constant (Pepin et al 1999, García et al 2006.…”
Section: Condition Of Larvaesupporting
confidence: 68%
“…Canino et al 1991, Canino 1997, Rooker et al 1997, Kimura et al 2000, Chícharo et al 2003, Catalan et al 2006, Garcia et al 2006, Lee et al 2006, Malzahn et al 2007). When fish size and water temperature between sites are similar, interpretation of results is straightforward: the group with the higher RD is in better condition since it contains more machinery (potential) for protein synthesis.…”
Section: Effect Of Fish Size and Temperature On The Use Of Rd As A Comentioning
confidence: 99%